Application of carbon nanoparticles in endoscopic thyroid cancer surgery: a systematic review and meta-analysis - He, Jiaxi; Sun, Pengfei; Lin, Jianhuang; Shen, Jiali; Lin, Huihui; Jiang, Hongzhan; Qiu, Rongliang; Lin, Ende; Lu, Yizhuo (Frontiers in Surgery, 2024)
Background: There has been a substantial increase in incidence of thyroid cancer globally over the past three decades, emphasizing the necessity for efficient surgical management. Surgical intervention requires meticulous lymphatic dissection; however, it is challenging to both accurately identify lymph nodes and preserve the surrounding structures. We investigated the role of carbon nanoparticles in endoscopic thyroid cancer surgery to improve surgical effects and reduce postoperative complications.Methods: Chinese and English literature databases from inception to May 2023 were searched based on inclusion criteria, and data were extracted independently by two investigators. STATA software was used for data analysis.Results: A comprehensive systematic review and meta-analysis were conducted with 13 publications (9 randomized and 4 non-randomized controlled trials). The results demonstrated that the application of carbon nanoparticles in thyroid surgery led to an increase in the number of retrieved lymph nodes and identification of metastatic lymph nodes. Furthermore, it considerably reduced the rate of improper parathyroidectomy and the incidence of postoperative hypocalcemia.The application of carbon nanoparticles can effectively improve the effects of surgical treatment, can enhance the identification of intraoperative lymph nodes, reduce postoperative complications, and protect the integrity and function of the parathyroid gland.